Impact of HIV testing on sexual health communication in South Africa. - Scott-Sheldon, Lori A J; Carey, Michael P; Carey, Kate B; Cain, Demetria; Vermaak, Redwaan; Mthembu, Jacqueline; Harel, Ofer; Simbayi, Leickness C; Kalichman, Seth C (Sexually transmitted infections, 2011)
The South African government recently launched a national campaign to test 15 million South Africans for HIV by 2011. Little is known about how receipt of HIV testing might influence interpersonal communication. To explore these questions, the authors examined the effects of prior HIV testing on sexual health communication among South Africans.
Keywords: Adult; Condoms; Disclosure; Female; Health Communication; HIV Infections; Humans; Male; Risk Factors; Sexual Behavior; South Africa